GAMBARAN KONSELING YANG DIPEROLEH PADA KUNJUNGAN NIFAS KE-4 DI WILAYAH KERJA PUSKESMAS ROWOSARI 1 KABUPATEN KENDAL - Titik Sapartinah; Ana Sundari (Midwifery Care Journal, 2020)
The postpartum period is a transition period for the mother, baby and family physiologically, emotionally and socially. The low quality of health services can lead to low success in health promotion and early detection and adequate management of problems from diseases that arise in the postpartum period. The aim of the study was to described the counseling obtained by postpartum mother at the fourth postpartum visit. This study uses a descriptive method, with a survey approach. The population was all post-partum mothers who received the fourth postpartum attendance in the area in Public Health Care of Rowosari 0I. The number of samples was 34 respondents. The sampling technique used saturated samples. The results showed that the counseling was obtained at the fourth postpartum visit was still based on the complication history of the puerperium period which was still not good (76.47%), and based on family planning counseling that was still not good (79.41%). The midwives should assessing the mother complications and providing family planning counseling